Unraveling the microbial mysteries: gut microbiota’s role in ulcerative colitis - Ren, Keyu; Yong, Chunming; Jin, Yanchun; Rong, Shanwei; Xue, Kuijin; Cao, Bin; Wei, Hongyun (Frontiers in Nutrition, 2025)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease characterized by persistent inflammation of the colon. Recent research has highlighted the significant role of gut microbiota in the pathogenesis and treatment of UC. This review aims to provide a comprehensive overview of the current understanding of the relationship between gut microbiota and UC. We discuss the involvement of gut microbiota in the onset of UC, including the dysbiosis observed in patients and its potential mechanisms. Additionally, the role of extra-intestinal microbiota in UC pathogenesis is explored, which has been less studied but is gaining attention. The influence of gut microbiota on the efficacy of biological immunotherapy for UC is also examined, highlighting how microbial composition can influence treatment outcomes. Furthermore, we review microbiota transplantation, and their potential benefits in UC management. Finally, we consider the combined use of antibiotics and biological agents in UC treatment, discussing their synergistic effects and potential drawbacks. This review underscores the importance of gut microbiota in UC and suggests that targeting microbial communities could offer new avenues for effective treatment.